'London streets' app prototyping and the user experience. (2016) - Fishenden, Jerry
This article describes the practice-based and practice-led research and development of an initial version 1.0 mobile phone and tablet application focused on the historic origins of City of London streets. The app is designed for both the iOS and Android mobile operating systems and developed using the cross-platform Corona SDK. It forms part of ongoing research into the user experience of the past of place and the application of an iterative methodology for acquiring and applying continuing user feedback and improvement. Future articles will detail the development of the application beyond version 1.0, including the role of user feedback in its further refinement, improvement and development.